Microbial maintenance energy quantified and modeled with microcalorimetry. Issue 9 (23rd June 2022) - Hunt, Kristopher A.; von Netzer, Frederick; Gorman‐Lewis, Drew; Stahl, David A.
Abstract: Refining the energetic costs of cellular maintenance is essential for predicting microbial growth and survival in the environment. Here, we evaluate a simple batch culture method to quantify energy partitioning between growth and maintenance using microcalorimetry and thermodynamic modeling. The constants derived from the batch culture system were comparable to those that have been reported from meta‐analyses of data derived from chemostat studies. The model accurately predicted temperature‐dependent biomass yield and the upper temperature limit of growth for Desulfovibrio alaskensis G20, suggesting the method may have broad application. An Arrhenius temperature dependence for the specific energy consumption rate, inferred from substrate consumption and heat evolution, was observed over the entire viable temperature range. By combining this relationship for specific energy consumption rates and observed specific growth rates, the model describes an increase in nongrowth associated maintenance at higher temperatures and the corresponding decrease in energy available for growth. This analytical and thermodynamic formulation suggests that simply monitoring heat evolution in batch culture could be a useful complement to the recognized limitations of estimating maintenance using extrapolation to zero growth in chemostats. Abstract : We developed a novel method that combines microbial batchcultures with microcalorimetry to quantify the changing partitioning of metabolicenergy between growth and maintenance of cellular viability under increasinglyrestrictive growth conditions, in this study determined by growthtemperature. A mathematical model basedon fundamental growth relationships and parameter estimates was predictive ofgrowth behavior over a wide range of temperatures and now provides a frameworkfor extending this experimental format to other organisms, systems, and stressconditions.